Trends in Income-Related Gaps in Enrollment in Early Childhood Education - Katherine Magnuson; Jane Waldfogel (SAGE Publishing, 2016)
We use data from the 1968-2013 October Current Population Survey to document trends in 3- and 4-year-old children's enrollment in center-based early childhood education, focusing on gaps in enrollment among children from low-, middle-, and high-income families. We find that income-related gaps in enrollment widened in the 1970s and 1980s but appear to have plateaued or narrowed for succeeding cohorts. These patterns are consistent with recent trends in income-related gaps in school achievement.